Evaluation of patients' adherence in accordance with guidelines for Peripheral Arterial Disease management - Michail Zografakis Sfakianakis; Michail Papanikolaou; Ioanna Alexaki; Evangelia Vasilaki; Emmanuel Androulakis; Theocharis Konstantinidis (Ene, 2017)
Introduction: Peripheral Arterial Disease (PAD) is a serious chronic disease of the lower limb circulatory system as it affects the activity daily living and reduces patients' quality of life. Usually, patients have low adherence to medication and guidelines. Aim: To access patients' adherence and attitude, after being given instructions for medication and guidelines on the modifiable risk factors. Methods: It is a descriptive cross-sectional observational study, with a sample of 101 patients, hospitalized in the vascular surgery ward of a tertiary hospital in Crete. Data were collected using a research datasheet that was constructed for the purpose of this study, following the current guidelines for PAD management. Also, the Medication Adherence Self-Efficacy Scale (MASES-R) questionnaire was used. For the statistical analysis, the IBM SPSS 20.0 program was used with a significance level set to p<0,05. Results: Among 101 patients, 78 patients (77,2%) were men. The mean age was 69(+13,5) years. Body Mass Index (BMI) was 29(+5,2). From 72 patients (71,3%) who were smokers, despite of recommendations, 41 (41,8%) were non-compliant and continued smoking. Only 15.8% were fully aware (5/5 correct answers) of their disease. The 52,5% of patients did not take their medication themselves. Intermittent claudication in the first 50 meters of walking was found in 70,4% of the sample. There was a statistically significant correlation between the period (in years) that patients suffered from diabetes mellitus and the occurrence of peripheral neuropathy (p=0,038). A negative correlation between patients' age and disease awareness was observed (Δ= -0,344. p<0,001 Somers' d). Conclusions: Adherence to the guidelines deviates significantly from what is recommended, as patients were unable to follow a lot of the instructions given by healthcare professionals. Therefore, nurses should initially focus on adequate patients' education about their disease. Interventions such as scheduled patient monitoring, weight loss programs and smoking cessation programs should be implemented, to achieve improved adherence, aiming to a greater decrease in morbidity.